2009
DOI: 10.1080/09500690903100265
|View full text |Cite
|
Sign up to set email alerts
|

Confidence versus Performance as an Indicator of the Presence of Alternative Conceptions and Inadequate Problem‐Solving Skills in Mechanics

Abstract: This study investigated the use of performance-confidence relationships to signal the presence of alternative conceptions and inadequate problem-solving skills in mechanics. A group of 33 students entering physics at a South African university participated in the project. The test instrument consisted of 20 items derived from existing standardized tests from literature, each of which was followed by a self-reported measure of confidence of students in the correctness of their answers. Data collected for this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 23 publications
2
14
0
2
Order By: Relevance
“…This analysis method that is also known as Certainty of Response Index (CRI) had been done by some researchers, e.g. Hasan et al (1999) and Potgieter et al (2010). The method used for the analysis of students' understanding level in this research referred to the method employed by Sutopo (2016) who adapted the method utilized by Potgieter et al (2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis method that is also known as Certainty of Response Index (CRI) had been done by some researchers, e.g. Hasan et al (1999) and Potgieter et al (2010). The method used for the analysis of students' understanding level in this research referred to the method employed by Sutopo (2016) who adapted the method utilized by Potgieter et al (2010).…”
Section: Methodsmentioning
confidence: 99%
“…Hasan et al (1999) and Potgieter et al (2010). The method used for the analysis of students' understanding level in this research referred to the method employed by Sutopo (2016) who adapted the method utilized by Potgieter et al (2010). Based on their answers, the levels of students understanding were grouped into 4 categories.…”
Section: Methodsmentioning
confidence: 99%
“…The authors concluded that the method could be easily employed to differentiate alternative conceptions from a lack of knowledge. Then, the method was used to distinguish a lack of knowledge from alternative conceptions in mechanics (Planinic, Boone, Krsnik, & Beilfuss, 2006;Potgieter, Malatje, Gaigher, & Venter, 2010); simple direct-current circuits (Peşman & Eryılmaz, 2010;Planinic et al, 2006); radioactivity (Colclough, Lock, & Soares, 2011); diffusion and osmosis (Odom & Barrow, 2007); and environmental education (Arslan, Çiğdemoğlu, & Moseley, 2012). The review of these studies suggests that the Hasan et al 's method can be employed to distinguish a lack of knowledge from alternative conceptions.…”
Section: Confidence Judgements In Science Education Researchmentioning
confidence: 99%
“…Commonly, a respondent is then requested to indicate the degree of certainty she/he has in her/his ability to select and use well-established knowledge, concepts and rules to arrive at each answer (Potgieter, Malatje, Gaigher, & Venter, 2010). Confidence is most often measured on a scale, in our case 1 -4, where 1 implies a total guess and 4 a complete confidence.…”
Section: Confidence Of Responsementioning
confidence: 99%
“…However, if the confidence is high and the answer wrong it indicates a misplaced confidence in the person's knowledge on the particular subject matter, either suggesting a misjudgement of her/his own ability or a sign of existing misconceptions. A confidence measure, together with the correctness or not of a response can thus be used to distinguish between a lack of knowledge and either over-confidence or the existence of a misconception (Potgieter et al, 2010).…”
Section: Confidence Of Responsementioning
confidence: 99%